A new species of the Neotropical genus Itatingamyia Albuquerque (Diptera: Muscidae) - Haseyama, Kirstern L. F.; de Carvalho, Claudio J. B. (Zootaxa, 2011)
Itatingamyia (Muscidae: Diptera) was known from a single species and eight specimens. This paper describes a new species, Itatingamyia couriae sp. nov. (Santa Teresa, Espírito Santo, Brazil), and provides an identification key for the two species of Itatingamyia.